La Règle de Marie caractère littéraire et inspiration monastique - Beyers, Rita 1951- (2011)
Chapter 6 of Pseudo-Matthew contains the famous description of Mary’s life in the Temple of Jerusalem between the ages of three and fourteen. The description is typical of the Latin tradition of the Protevangelium of James and the version found in Pseudo-Matthew is an adaptation of an earlier description, traces of which are preserved in the Irish Liber Flavus Fergusiorum. Mary is said to have introduced a rule of life for herself, which is, traditionally, regarded as a reference to the Rule of Benedict, and, at the same time, as giving a terminus a quo for dating the Pseudo-Matthew, i.e. after the middle of the sixth century. This paper analyses chapter 6 in light of the early monastic rules and argues that, despite the undeniable monastic overtones, it cannot be read as an evocation of real monastic life. Rather than being rooted in the great monastic experience of the early Middle Ages, the description is to be considered a literary portrait. The portrait of Mary’s ascetic life sketched by Ambrose in his De virginibus 2, 2, 6-19 appears to be an appropriate model.
Keywords: Neutestamentliche Apokryphen; Protoevangelium Jacobi